2014
DOI: 10.1002/etc.2640
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of soil–water sorption coefficients of volatile methylsiloxanes

Abstract: The sorption behaviors of 4 cyclic and linear volatile methyl siloxane (VMS) compounds between water and organic matter in 3 United Kingdom soils were studied by a batch equilibrium method using13C-enriched sorbates. Sorption and desorption kinetics and isotherms were determined for octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), octamethyltrisiloxane (L3), and decamethyltetrasiloxane (L4). Concentrations of [13C]-VMS in the soil and aqueous phases were measured directly by extraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 40 publications
11
50
2
Order By: Relevance
“…Thus, when adequately trained, LFERs have wider domains of applicability, which can include VMS. 42 The same conclusion has been reached by other researchers for different organic compounds. 64,67 VIII.2.…”
Section: Environmental Implicationssupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, when adequately trained, LFERs have wider domains of applicability, which can include VMS. 42 The same conclusion has been reached by other researchers for different organic compounds. 64,67 VIII.2.…”
Section: Environmental Implicationssupporting
confidence: 81%
“…In a laboratory study, a batch equilibrium method based on OECD test guideline 106 41 was employed. 42 The measured log K OC values as listed in Table 8 demonstrated a general trend of increasing log K OC as the molar mass of VMS increases, similar to that of log K OW . In addition to the wellcontrolled laboratory study cited above, K OC values were also measured in isolated soil organic matter/water systems, 43 and river water/sediment systems.…”
Section: Soil/water Distribution Coefficientsmentioning
confidence: 64%
“…Previous experimental studies have reported considerably lower log K OC values that range from 4.98 to 6.33 for D 5 . 10,11,16 These values for D 5 are all more than 1 order of magnitude lower than the estimate from the Seth regression. Existing SP-LFERs fail to provide good estimates for cVMS because SP-LFERs implicitly assume that controlling interactions are identical for all chemicals.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Evidence of the steric hindrance of the ring structure of cVMS reducing the potential for London forces and dipole−induced dipole interactions can be found in comparing the log K OC of the cyclic D 4 to linear decamethyltetrasiloxane (L 4 ). Kozerski 16 Differences in Sorption between OC and DOC. As discussed above, cVMS have a lower L compared to other chemicals with similar V. For that reason, we focused the comparison of OC and DOC on their differences in v and l. In the PP-LFER equations that include cVMS in the training set v DOC is slightly larger than v OC (1.84 and 1.76) (Figure 3) implying that the energy cost for cavity formation on the water Environmental Science & Technology Article side will be slightly higher in a K DOC system than in a K OC system.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Table provides a summary of the recommended physical and chemical properties of D5, including key intermedia partitioning and degradation properties (i.e., half‐lives). A more detailed discussion on methods for determining these properties and justification of these recommended properties and their temperature dependence is given in Kozerski et al , Xu and Kropscott , and Xu et al . In the present study, we focus on aspects of these properties that are of particular importance for evaluating fate and transport.…”
Section: Step 2: Physical Chemical and Degradation Propertiesmentioning
confidence: 99%